Contemporary accounting : a conceptual approach : study guide - Rhyn, Diane van. (South Melbourne : Nelson ITP, 1999)
This book is about: Introducing to accounting; The conceptual framework; Wealth and the measurement of profit; The balance sheet; ...
Keywords: Accounting; Accounting -- Australia; Accounting -- AustraliaxProblems, exercises, etc; Accounting -- Study and teaching (Higher) -- Australia